Sensory attenuation abnormalities and intervention strategies in patients with schizophrenia - Zhou Aibao; Li Zekai; Huang Yalian; Hu Tao (Sichuan jingshen weisheng)
Prior research has demonstrated significant deficits in sensory attenuation in patients with schizophrenia， which is a phenomenon that pertains to their inability to adequately modulate the intensity of sensory feedback associated with self-initiated voluntary actions. Sensory attenuation， a fundamental aspect of the sense of agency， is crucial for individuals to accurately perceive their own actions and effectively adapt to the external environment. Investigation on this phenomenon sheds light on the intricate mechanisms underlying sensory information processing deficits in patients with schizophrenia. This paper comprehensively examines the intricate relationship between abnormal sensory attenuation and the early identification of schizophrenia， delves into the underlying mechanisms that give rise to these abnormalities， and explores intervention strategies specifically designed to address them. Ultimately， our aim is to offer novel perspectives and insights that can contribute to the advancement of diagnosis and treatment of schizophrenia. ［Funded by Regional Project of National Natural Science Foundation of China （number， 32160202）］